Allium ahmet-tirasii (Amaryllidaceae), a new species from Southern Anatolia (Türkiye) - Yildirim, Hasan; Özdöl, Tuğkan; Erdem, Seval (Phytotaxa, 2024)
Allium ahmet-tirasii Yıldırım (Amaryllidaceae) is described as a new species from Alanya district in Antalya province, southern Türkiye. Diagnostic characteristics, a full description, and comprehensive illustrations are provided. Based on morphological features, it belongs to the Allium subgen. Polyprason sect. Scorodon. Allium ahmet-tirasii has no closely related species. It slightly resembles A. sivasicum, by the pale brownish-orange inner tunic and greenish-yellow perigone and A. opacum, by perigone size and color also style length. However, it is easily distinguished from both A. sivasicum and A. opacum by many other morphological characters and its habitat. It is characterized by 1–2 equal bulblets; spathe one or sometimes 2-valved, if with 2-valved, valves unilateral; filaments equal or slightly shorter than tepals; style 1.5–2 mm long before fertilization shorter than perigone.